Is contrarian investment producing higher returns for value investors? - Lopes, Manuel Fernando Lourenço (2023)
This dissertation addresses the complex area of decision-making related to stock valuation. The study will focus on value investing and the contrarian investment approach, investigating whether this strategy provides investors with higher returns. The concept of margin of safety, introduced by Klarman (1991), is also discussed, relating it to defensive investment, such as the importance of identifying undervalued or overvalued stock. Furthermore, this research addresses the role of emotions and irrational investor behaviour in stock price formation and how these factors can create opportunities for investors seeking contrarian investment approaches. The findings suggest that contrary to past literature that advocated for higher returns with a value investment strategy, the observed data during the analysed time period may not be able to confirm the continuity of this trend as previously reported, revealing a diminishing correlation between contrarian investment strategies and investment returns. With the limitations of this study and the small sample used, the sample should be increased for further study to get more robustness to the conclusions. While the study did not confirm the effectiveness of value investing during the analysed period, it is essential to note that these findings are specific to that period. Given the significant shifts in the macroeconomic and market landscape in 2022-2023, the dynamics of value investing may evolve again.